Inovasi Peternakan Berkelanjutan melalui Teknologi Silase dan Edukasi Kesehatan Ternak di Desa Linggasari - Putri Dian Wulansari; Agung Maulan; Asep Nurhotman; Karina Qiraatul Kaffah; Rafiah Rafiah; Teza Arfan; Syifa Puspita; Anisa Safari; Uci Ismawati (Journal of Empowerment Community, 2026)
This community service program aimed to enhance the capacity of livestock farmers in Linggasirna Village, Sariwangi District, Tasikmalaya Regency through the application of rice straw silage technology and livestock health education. The activity was conducted as part of the Community Service Program (KKN) of Universitas Perjuangan Tasikmalaya from July 22 to August 26, 2026, involving 15 students from five faculties in collaboration with local cattle and goat farmers. The methods employed included community education, technology diffusion, and hands-on technical training. The results indicated that the implementation of rice straw silage technology effectively improved farmers’ skills in processing agricultural waste into high-nutrient and storable alternative feed, thereby reducing dependence on fresh forage during the dry season. Furthermore, livestock health and welfare education increased farmers’ awareness of biosecurity, sanitation, and hygienic waste management practices. The participatory, practice-based approach proved effective in facilitating knowledge and technology transfer while strengthening collaboration among students, academic supervisors, and the local community to promote a more productive and sustainable smallholder livestock system.